Cognitive Event-Related Potentials in Psychopathology: New Experimental and Clinical Perspectives - Salvatore Campanella (Frontiers Research Topics, 2017)
A common feature of many psychopathological states (going from anxiety, depression to schizophrenia or addictions) is to show cognitive alterations. These cognitive deficits clearly impact on the onset of clinical symptoms. Therefore, recent studies showed that increasing cognitive skills have a positive effect on patients' quality of life, and decrease the severity of clinical symptoms. However, a main problem consists in the fact that some minor cognitive restrictions, even if not observable at the behavioral level, may induce a state of "vulnerability" that can, in some circumstances, lead the patients to relapse. For instance, in alcohol dependence, it is well-known that, despite detoxification cure, psychological intervention and medication, 50 to 90% of patients resume in alcohol consumption within 1 year post-detoxification cure. In this view, it could be really important to find biological markers for even minor cognitive alterations, that can help clinicians to identify which patients are more "at-risk" to relapse, in order to improve treatment through best suited medication and specialized programs of cognitive rehabilitation. In this topic, our aim is to illustrate how and why cognitive event-related potentials (ERPs) may help in different psychopathological populations to adapt the treatment of individual patients on the basis of their specific neuro-cognitive alterations.